MEMPERKENALKAN SEJARAH PAHLAWAN NASIONAL KH. ABDUL HALIM BAGI PESERTA DIDIK MI/SD DI INDONESIA - aulia chairunnisa (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
Abdul Halim was a very influential person at that time because of the many programs (thoughts) he created that could benefit the local people. The community also agrees with what he is doing because it is a positive thing in order to build a better society / life. The purpose of conducting this research is so that we can find out the national heroes who have fought for the life of their nation and country so that we can remember and appreciate the services he had done at that time. The obstacle we face is that sometimes we forget that the heroes don't even know about their biographies because they don't know their history. In this research method, we have to read a lot of history books and attend hero museums because besides we are happy, reflexing our brains / minds, we can also learn about history directly from the events that have been done by heroes who have fallen before us. And we must be quite proud, grateful because there are still people who care about this nation and this country to keep standing even though the condition of the Indonesian state is still not independent (colonized) by other nations. For that we must cultivate a spirit of nationalism by studying hard and taking an active role in building this country into a developed country. This study discusses the concept of as-salam, ishlah al-samaniyah, the concept of santi funny, the concept of intisa.